PENGARUH PEMBIAYAAN PERBANKAN SYARIAH TERHADAP PERTUMBUHAN EKONOMI SUMSEL - Hairunnisa; Inda Fitri Utami; Siti Nurrohmah; Miranti (Program Studi Perbankan Syariah, 2022)
In times like today, the role of Islamic Banking is very important in the economy as part of the national banking system. Not only as an alternative solution in dealing with global economic turmoil that is increasingly difficult to predict, Islamic Banking also has a special role to encourage economic growth in a country, especially Indonesia with the largest Muslim majority population in the world. The purpose of this study was to get an idea of how the influence of Islamic banking financing in South Sumatra on the regional economic growth of South Sumatra. This research uses quantitative research methods. With the existence of Islamic banking, it is expected to increase the economic growth of the people in the South Sumatra Region.